Synthesis and characterization of curcumin-encapsulated loaded on carboxymethyl cellulose with docking validation as α-amylase and α-glucosidase inhibitors - Almehizia Abdulrahman A.; Al-Omar Mohamed A.; Al-Obaid Abdulrahman M.; Naglah Ahmed M.; Bhat Mashooq A.; Ghabbour Hazem A.; Khatab Tamer K.; Hassan Ashraf S. (Polish Journal of Chemical Technology, 2024)
In reaction to the expanding predominance of diabetes mellitus, curcumin nanoparticles stacked on carboxymethyl cellulose (CMC) composite were effectively synthesized, characterized, and examined utilizing UV/Vis and FTIR spectroscopy combined with transmission electron microscopy (TEM). The bioactivity of curcumin (Cur), carboxymethyl cellulose (CMC), and curcumin nanoparticles stacked with carboxymethyl cellulose (CUR-CMC) was tried through atomic docking approval as an α-amylase and α-glucosidase inhibitor. The conclusion illustrated that the curcumin-supported CMC is more potent than CUR itself self the validation presented is compared with acarbose as a reference molecule and then CUR-CMC can presented as promising in curing hyperglycemia by decreasing the absorption of glucose.